Reproduksi Ikan Betok (Anabas testudineus Bloch, 1792) Di Rawa Wasur Taman Nasional Wasur Kabupaten Merauke - Norce Mote; Ita Mattaru; Chalvyn Silasa Pakidi (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Climbing perch (Anabas testudineus Bloch, 1792), one of the types of fish that is able to survive in freshwater and brackish water, which belongs to the type of Blackwater fish. The study aims to determine the reproduction of Climbing perch (Anabas testudineus Bloch, 1792) at Wasur Swamp. The fish sampling was conducted in May to July 2019, with catching using a mesh of gills measuring the net-size 2.5 cm. Analysis used is the genital ratio, the maturity level of gonads (TKG), the Maturity index gonads (IKG) and fecundity. The whole fish was acquired during the study amounting to 380 tails consisting of 211 males and 169 females. The genital ratio gained during the study was 1.2:1. The spawning peak for three months of observation of the female fish of TKG IV occurred in May at the I Station. The fecundity of the Climbing perch ranges from 1.984 to 73.795, at a total length range of 105–159 mm and a total weight of 28 - 84 grams.Key Words: Climbing perch; Anabas testudineus; Reproduction; Wasur Swamp